Knowledge, practice and needs of family caregiver in the care of older people: a review - Ab Ghani, Nor Nadiya; Makhtar, Aniawanis; Syed Elias, Sharifah Munirah; Ahmad, Norfadzilah; Mohamed Ludin, Salizar (IIUM Press, 2022)
Family caregivers play a significant role in the care of older people. However, their knowledge, practice and needs in the care of older people often overlooked. Therefore, this review was performed to provide an overview of family caregivers’ knowledge, practice and needs in the care of older people. A literature search was conducted using the following electronic databases: ProQuest Health and Medical Complete, Wiley Online Library, EBSCO Host, Science Direct and Scopus. Search terms used were “older people”, “family caregiver”, “knowledge”, “practice” and “needs”. Two reviewers independently screened the studies and the extracted data. A total of 2115 eligible studies were identified after database search. Only nine studies met the inclusion criteria after full article screening and were included for data extraction. This review of the articles presents a summary of (1) family caregivers’ knowledge about the care of older people, (2) family caregivers’ practice in the care of older people and (3) family caregivers’ needs in the care of older people. The analysis reveals that most of the caregivers addressed a lack of knowledge and poor practice in the care of older people. This review also offers important insight into the needs of family caregivers. Hence, this review recommends further studies on knowledge, practice and needs in the care of older people to identify contextual challenges and provide evidence-based solutions to improve family caregivers’ knowledge, practice and needs in the care of older people.